Manajemen Sekolah Dalam Implementasi Kurikulum 2013 di Sekolah Dasar Guppi Uswatun Hasanah Pematang Siantar - Endang Manullang, Rasmauli Saria; Sulasmi, Emilda; Siregar, Astri Novia (UMSU, 2024)
The aim of this research is to find out (1) school management in implementing the 2013 curriculum at the GUPPI Uswatun Hasanah Pematang Siantar school; (2) To find out the obstacles faced by school management in implementing the 2013 curriculum; (3) To find out efforts to overcome obstacles to implementing school management in implementing the 2013 Curriculum. The research method used was a qualitative approach using case study research. The findings of the research results were: (1) School Management in implementing the 2013 Curriculum includes: Implementation of 2013 Curriculum management includes: Planning by holding KKG teachers to prepare Prota, Prosem, RPP. Implementation of implementing learning activities according to the RPP, the learning method is scientific, the principal carries out class monitoring. Assessment is carried out with daily assessments, mid-semester assessments and final semester assessments where the head of the assessment is not much different from the Merdeka Curriculum assessment which is currently taking place where the daily assessment is changed to formative, summative material coverage, and final material summative. (2) Constraints in school management in Implementation of the 2013 Curriculum, firstly, the mindset of teachers who have not implemented authentic assessment optimally; second, teachers' lack of proficiency in using ICT (Information, Communication, technology); thirdly, the completeness of subject books is still lacking; fourth, the large number of students. (3) Efforts to overcome obstacles in implementing the 2013 curriculum management at the GUPPI Uswatun Hasanah Elementary School include: first, conducting a 2013 chronicle workshop, utilizing KKG in each theme, secondly, obstacles that arise, such as when creating lesson plans, can be overcome together or assessment problems that are currently still a problem. is a teacher's difficulty, and thirdly creating a special application to help teachers in assessment.